Intra-Cystic Papillary Carcinoma of the Breast: Report of Three Cases - Nomenjanahary, Lalaina; Ralaivao, Rindra Andrianina; Randrianjafisamindrakotroka, Nantenaina Soa; Raivoherivony, Zo Irène (International Journal For Research In Biology & Pharmacy, 2020)
Intra-cystic papillary carcinoma of the breast is a rare malignant tumor. It represents less than 2% of all breast cancers, characterized by a slow growing with a good prognosis and low rate of local and distant recurrences. Three cases were collected in Department of Pathology at JRA University Hospital. The aim was to report the epidemiological and histopathological features of the lesion through the review of literature. The patients, two women and one man, were respectively 63, 80 and 75 years old. Clinically, it manifested as a breast mass. The lesions were on the left side in 2 cases (women’s cases). For the man’s case, the lesion was on the right side and he was undergone for excisional biopsies. The histological diagnosis was intra-cystic papillary carcinoma. Diagnosis of intra-cystic papillary carcinoma of the breast may be difficult at classical histological examination and identification of the myoepithelial cell layer by immunohistochemical study is helpful.